Compreendendo a sexualidade infantil nas relações de gênero: o lúdico como estratégia educativa - Moreira, Daniela Arroyo Fávero [UNESP] (2015)
Sexuality is an important concept because it is part of human development and goes beyond the sexual act, it involves personal manifestations (impulses and desires) and external influences (culture). Address this issue with children is important because they are social subjects in training. Gender issues, sex education and sexuality are important and needed to be worked in the classroom, especially at school indeed be a prime location in the information of the mediation process, but is also necessary for the family to talk to the children in this regard consciously, without fanciful explanations, for better ownership of specific knowledge. Based on the foregoing, the aim of this study was to understand infantile sexuality in gender relations, through the representations of educators, family and teacher and exercise play situation for children in a room of the 1st year of primary school, in a public school located in the state of São Paulo. The study also one (01) teacher and 22 (twenty two) family and 02 (two) parents and twenty (20) mothers. The instruments used for empirical research were: interview, questionnaire, diary and recreational activities. For this study the principles of historical-cultural theory were followed. The data were analyzed qualitatively. Data analysis together with the family allows us to demonstrate that they have pointed out significant differences in the behavior and personality of boys and girls from gender differentiation. On the analysis of the data conducted with the teacher, it was revealed that they are respected and taken into account the individual peculiarities of pupils and students with regard to clarification of doubts and limitations on the understanding of sexuality. Regarding the recreational activities we find that they enable teaching and learning relations in the formative processes of students in relation to gender and sexuality issues. In conclusion ...